Phát triển năng lực dạy học phân hóa cho sinh viên ngành sư phạm Mĩ thuật: một nghiên cứu tổng quan - Nguyễn, Thị Hồng Thắm; Quách, Thị Ngọc An (Tạp chí Giáo dục, 2025)
The requirements of educational innovation require teacher training schools to improve the quality of training, focusing on developing differentiated teaching capacity for pedagogical students. By analyzing, synthesizing, and systematizing documents, the article summarizes studies on differentiated teaching competence and developing differentiated teaching competency for Fine Arts pedagogical students. The article has identified gaps in research on differentiated teaching capacity, proposed potential future research directions for Fine Arts teacher training institutions in Vietnam, thereby contributing to improving the effectiveness of developing differentiated teaching competence for Fine Arts pedagogical students.